Societal Boundaries Suppressing Inner Talent in The Pregnant King By Devdutt Pattanaik - Anju Grewal; Dr.Mohd. Nazzar (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2024)
This research paper examines Devdutt Pattanaik’s novel The Pregnant King with a focus onto how societal norms and cultural expectations become significant barriers for various characters within the narrative. The paper explores how these societal boundaries constrain the lives and potential of the characters in multiple ways. Using textual analysis and character studies, the paper delves into the journey and challenges faced by different characters. The findings illustrate how Pattanaik’s narrative challenges conventional norms and raises questions about the impact of societal boundaries and gender biasedness. By re-evaluating the boundaries and expectations imposed on individuals by social norms, this study contributes to ongoing discussions surrounding gender, self-expression, and cultural interpretations of identity in literature and beyond.